Capoeira Connections A Memoir in Motion (University Press of Florida, 2023)
This book is freely available in an open access edition thanks to TOME (Toward an Open Monograph Ecosystem)-a collaboration of the Association of American Universities, the Association of University Presses, and the Association of Research Libraries-and the generous support of Duke University.A portrait of the game of capoeira and its practice across borders Originating in the Black Atlantic world as a fusion of dance and martial art, capoeira was a marginalized practice for much of its history. Today it is globally popular. This ethnographic memoir weaves together the history of capoeira, recent transformations in the practice, and personal insights from author Katya Wesolowski's thirty years of experience as a capoeirista.Capoeira Connections follows Wesolowski's journey from novice to instructor while drawing on her decades of research as an anthropologist in Brazil, Angola, Europe, and the United States. In a story of local practice and global flow, Wesolowski offers an intimate portrait of the game and what it means in people's lives. She reveals camaraderie and conviviality in the capoeira ring as well as tensions and ruptures involving race, gender, and competing claims over how this artful play should be practiced. Capoeira brings people together and yet is never free of histories of struggle, and these too play out in the game's encounters.In her at once clear-sighted and hopeful analysis, Wesolowski ultimately argues that capoeira offers opportunities for connection, dialogue, and collaboration in a world that is increasingly fractured. In doing so, capoeira can transform lives, create social spheres, and shape mobile futures.Katya Wesolowski is lecturing fellow of cultural anthropology and dance at Duke University.Publication of this work made possible by a Sustaining the Humanities through the American Rescue Plan grant from the National Endowment for the Humanities.